KOTZÉ, Willem Daniël Inventory of documents - KOTZÉ, Willem Daniël (ARCA, 2018)
Private papers of W.D. Kotzé, National Party MP, Odendaalsrus [1970-1974], Parys [1974-1982], Ambassador in Bophuthatswana [1982-1992]
COVERAGE 1961-1979; 300 Files; 12,44 Metres.
Keywords: KOTZÉ, Willem Daniël; Inventories; Politicians; National Party